SELECTING THE MANAGEMENT OF PATIENTS WITH CHRONIC HEPATITIS B AFTER THE COMPLETION OF THE LONG-TERM ANTIVIRAL THERAPY - E. V. Esaulenko; K. A. Zakharov; I. S. Alikian; A. A. Sukhoruk; T. A. Stasishkis; A. U. Kovelenov (Журнал инфектологии)
Study aims: The study purpose was to analyze the results of the clinical and laboratory monitoring of HBeAg-negative chronic hepatitis B patients after discontinuation of longterm nucleosides analogues antiviral therapy in order to determine further management.Materials and methods: A retrospective-prospective investigation was performed in 106 patients with diagnosis of HBeAg-negative chronic hepatitis B during the course of antiviral therapy using nucleosides analogues. Average treatment duration was 190,1±77,7 weeks. The therapy was discontinued for 29 patients in the period of time from two to five years of the treatment, they were followed up from 6 months to 6 years. The activity of aminotransferases, the levels of HBV DNA were evaluated, the liver elastometry was performed during the patients monitoring. The relapse of disease after the treatment discontinuation was considered when the viral load exceeded 2.0x103 IU / ml and/or alanine aminotransferase levels were above the reference values.Results: The viral load varied from 4,0х102 IU/ml to 2,87 х 107 IU/ml at 86,2% cases after the 6 months of discontinuation of the treatment. However median levels of viral load were not higher than 2,5 х 103 IU/ml at different timepoints of observation. The VL was higher than 2,0 х 103 IU/ml in 62,1% patients and it matched to relapse criterion. Clinical relapse was not revealed in 13,8% cases at observational period from 6 months to 2 years. The second course of antiviral therapy was not required for 37,9% patients, at the same time it was necessary to consider it for the rest ones.Conclusion: Regular medical checkups with periodical clinical, laboratory and instrumental examinations after antiviral treatment discontinuation are required for timely detection of relapse and decision regarding the next course of antiviral therapy.